2020
DOI: 10.1200/jco.2020.38.15_suppl.3566
|View full text |Cite
|
Sign up to set email alerts
|

Platform comparison of HTG EdgeSeq and RNA-Seq for gene expression profiling of tumor tissue specimens.

Abstract: 3566 Background: Clinical biomarker studies are often hindered by the availability of tissue specimens of sufficient quality and quantity. While RNA-Seq is often considered the gold standard for measuring mRNA expression levels in cancer tissue, it typically requires multiple formalin-fixed paraffin-embedded (FFPE) tissue sections to extract a sufficient amount of quality RNA for subsequent gene expression profiling analysis. The HTG EdgeSeq technology is a gene expression profiling platform that combines qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This agrees with recent data from Ran et al ., where targeted sequencing was validated against bulk RNA sequencing for >1200 samples. 48 …”
Section: Discussionmentioning
confidence: 99%
“…This agrees with recent data from Ran et al ., where targeted sequencing was validated against bulk RNA sequencing for >1200 samples. 48 …”
Section: Discussionmentioning
confidence: 99%
“…In the initial publication, only a weak trend was observed between anti-tumor activity of loncastuximab tesirine and CD19 expression levels across ten cell lines that also included CD19-negative cells (10). Here, we expanded the number of cell lines analyzed and even when focusing on B cell lymphoma models only, we observed a significant correlation between the activity of loncastuximab tesirine and CD19 expression on cell surface as well as CD19 RNA levels, using multiple platforms including one specifically designed for the analysis of formalin-fixed paraffin embedded clinical specimens (34). So far, immunohistochemistry (IHC) performed on tumor samples from the loncastuximab tesirine phase 1 and the phase 2 trials have not demonstrated a correlation between CD19 expression and ORR, with patients with extremely low or no detectable CD19 IHC expression responding to loncastuximab tesirine (20,35).…”
Section: Discussionmentioning
confidence: 93%
“…In the initial publication, only a weak trend was observed between the anti-tumor activity of loncastuximab tesirine and CD19 expression levels across ten cell lines, including CD19-negative cells (11). Here, we expanded the number of cell lines analyzed, and even when focusing on B cell lymphoma models only, we observed a significant correlation between the activity of loncastuximab tesirine and CD19 expression on cell surface as well as CD19 RNA levels, using multiple platforms, including one specifically designed for the analysis of formalin-fixed paraffin-embedded clinical specimens (29). So far, immunohistochemistry (IHC) performed on tumor samples from the loncastuximab tesirine phase 1 and the phase 2 trials have not demonstrated a correlation between CD19 expression and ORR, with patients with extremely low or no detectable CD19 IHC expression responding to loncastuximab tesirine (17,30).…”
Section: Discussionmentioning
confidence: 96%